SEROLOGICAL STUDY BY USING THE ELISA TECHNIQUE TO IDENTIFICATION OF AVIAN INFECTIOUS BRONCHITIS DISEASE AMONG SOME FIELDS OF BROILER CHICKENS IN DIYALA PROVINCE. - Alazawy , Amer KH. (Diyala Agricultural Sciences Journal, 2013)
Infectious bronchitis (IB) is a common highly contagious viral disease of poultry; it causes major economic losses to the poultry industry. This study was conducted to investigate the prevalence of avian infectious bronchitis (IB) by evaluated the maternal derived antibodies (MDA) at 3 days of age and compared with the antibodies against the disease in 25 days of age, also to study the clinical signs and gross lesions of the suspected infected birds in some broiler chickens farms of Diyala governorate during the period from September 2012 to April 2013. Twenty broiler chicken flocks were reported in this study, blood samples were collected from each flocks two times to investigate the antibody titers by using Enzyme- Linked Immunosorbent Assay (ELISA). Significant variation (P<0.05) was observed in the means of antibody titers against IBV between the maternal derived antibodies at 3 days old and 25 days old, also 14 farms showed clinical signs of IB including mainly, severe respiratory signs with high morbidity and mortality, postmortem examination of affected flocks showed lesions mainly in trachea and kidney. The result of this study showed that IB was the most prevalence and widespread disease in broiler chickens farm particularly at 3 weeks of age. Therefore, because of the lack of a specific vaccine against endemic strains of IBV in Iraq, IB infection has remained a problem in the Diyala poultry farms.